Don't think about dinner : save time and money with 125+ easy, nourishing, delicious recipes for every meal - Lueke, Jenn (William Morrow, an imprint of HarperCollins, 2026)
Whether you want to improve your health, cut down food waste (and spending), reduce your mental load, or build new kitchen skills, Don't Think About Dinner provides everything you need to confidently approach every meal of the day--from shopping and stocking the pantry to storing and reheating leftovers, and everything in between. As a college student, Jenn was struggling with health problems and tired of quick-fix "healthy" recipes that relied on obscure, expensive ingredients that often spoiled before she could finish them. Overwhelmed and frustrated, she felt further from her health goals. In this engaging, cleverly organized book, Jenn expands on the content that has captivated millions of devoted follows. Unlike a typical cookbook, this comprehensive handbook offers strategies, tools, tips, meal plans, and more, plus over 125 delicious recipes. Jenn includes a wide range of adaptable dishes that suit any vibe, budget, or dietary need, from breakfast and lunch to appetizers, dinner, drinks, snacks, and desserts. --